Prophet Yunus and Big Fish - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
This beautifully illustrated board book, introduces to the children the greatest stories from the Quran and lessons to be learnt from them
Keywords: Islamic Book